1992
DOI: 10.1590/s0036-46651992000200011
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos ecológicos da leishmaniose tegumentar americana: 9. Prevalência/incidência da infecção humana nos municípios de Pedro de Toledo e Miracatu, São Paulo, Brasil

Abstract: Este trabalho apresenta aspectos epidemiológicos da leishmaniose tegumentar nos municípios de Pedro de Toledo e Miracatu, região do Vale do Ribeira, estado de São Paulo, referente ao período 1973-1984. Foi feita uma análise retrospectiva de 108 e 65 casos humanos, respectivamente, para os dois municípios acima. Outro estudo prospectivo foi realizado através do exame clínico e testes de Montenegro, imunofluorescência indireta (IF) e hemaglutinação passiva (HA). Duzentos e setenta e três pessoas foram examinadas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 14 publications
0
2
1
Order By: Relevance
“…This result was lower to that observed by Gomes et al (1992), in the Vale do Ribeira, São Paulo, where 10.2% (27/273) were seropositive, by Silveira et al (1996a) Among the seropositive there were women, children and people who reported that they performed only housework. These findings are in agreement with observations from the literature where the infection may be occurring in domiciliary and peridomiciliary area (CUNHA; LIMA; POMPEU, 2006;CORTE et al 1996;FALQUETO et al, 1986FALQUETO et al, , 1991GOMES et al, 1992;OLIVEIRA NETO et al, 1988).…”
Section: Discussioncontrasting
confidence: 65%
“…This result was lower to that observed by Gomes et al (1992), in the Vale do Ribeira, São Paulo, where 10.2% (27/273) were seropositive, by Silveira et al (1996a) Among the seropositive there were women, children and people who reported that they performed only housework. These findings are in agreement with observations from the literature where the infection may be occurring in domiciliary and peridomiciliary area (CUNHA; LIMA; POMPEU, 2006;CORTE et al 1996;FALQUETO et al, 1986FALQUETO et al, , 1991GOMES et al, 1992;OLIVEIRA NETO et al, 1988).…”
Section: Discussioncontrasting
confidence: 65%
“…However, in the current study the similar rates in males and females suggest the same risk of acquiring the disease. In Amaraji, in the Southern Zona da Mata in Pernambuco, the ATL transmission pattern differs from other areas of Brazil, since more males and adults were affected, suggesting extradomiciliary transmission in the workforce 8,12 .…”
Section: Discussionmentioning
confidence: 94%
“…Esses resíduos, em franco processo de degradação, obrigam as populações de reservatórios silvestres a procurarem o ambiente extraflorestal (peridomiciliar e domiciliar) em busca de alimentos. Processo semelhante ocorre com os vetores, que buscam no homem e animais domésticos a fonte alimentar de sobrevivência (GOMES et al, 1992;CARVALHO, 1994).…”
Section: Discussionunclassified
“…O município de Bela Vista do Paraíso possui 14.678 habitantes (IBGE, 2009) e está localizado na região Norte do Paraná a 429 Km de Curitiba (Latitude: 22º59'49 Sul e Longitude: 51º11'27" W-GR-GH e altitude de 528 metros) e a escolha deste município ocorreu pela constância de casos de LTA em humanos nos últimos anos, sendo a maioria no perímetro urbano. No período de fevereiro de 2000 a junho de 2004 ocorreram 61 casos autóctones de LTA, confirmados pela reação de Montenegro (Intradermoreação: IDR) (SINAN -Sistema de Informação de Agravos de Notificação) (dados não publicados).…”
Section: áRea De Estudo E Amostragemunclassified